Discrepancy between official records of the Brazilian National Immunization Program Information System and the household survey about vaccination coverage in Cubatão, São Paulo: cross-sectional study, 2023 - Luciana Martins Rozman; Ana Marli Christovam Sartori; Alexandra Azevedo Souza; Patricia Coelho de Soarez (Epidemiologia e Serviços de Saúde)
Abstract Objective To assess the concordance between vaccination data registered in the Brazilian National Immunization Program Information System and information in the vaccination booklets of children under 2 years of age who participated in the household survey of vaccination coverage in Cubatão, São Paulo. Methods This is a descriptive study comparing the doses registered in vaccination booklets with those in the Brazilian National Immunization Program Information System for children born in 2019 and 2020. Concordance was assessed regarding the doses applied and application dates recorded, using the Kappa test and the intraclass correlation coefficient. Results The household survey showed that vaccination coverage targets were achieved for all vaccines in the national immunization schedule for children under 2 years of age: 90.0% for BCG and human rotavirus, and 95.0% for other vaccines. When checking the same children in the information system, coverage was below 70.0%, and in 10.0% of them the application dates were inconsistent. Approximately 24.0% of the children were not entered in the information system, despite having their vaccinations recorded in their booklets. Conclusion The results indicate issues regarding accuracy and completeness of data from the Brazilian National Immunization Program Information System compared to vaccination booklets, highlighting challenges in vaccination records that may compromise monitoring of vaccination coverage in Cubatão.